2020
DOI: 10.1016/j.apenergy.2019.113965
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective techno-economic-environmental optimisation of electric vehicle for energy services

Abstract: Electric vehicles and renewable energy sources are collectively being developed as a synergetic implementation for smart grids. In this context, smart charging of electric vehicles and vehicle-to-grid technologies are seen as a way forward to achieve economic, technical and environmental benefits. The implementation of these technologies requires the cooperation of the end-electricity user, the electric vehicle owner, the system operator and policy makers. These stakeholders pursue different and sometime confl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 154 publications
(67 citation statements)
references
References 39 publications
1
66
0
Order By: Relevance
“…A quantitative analysis of how many users or sessions are affected by smart charging is largely lacking. This is particularly relevant as most pilots relate to residential (or private) charging rather than public charging [26,27]. Given that residential charging with one EV is more predicable than public charging (with several EVs with different charging characteristics on one charging station), applying smart charging on public charging infrastructure requires more research.…”
Section: Introductionmentioning
confidence: 99%
“…A quantitative analysis of how many users or sessions are affected by smart charging is largely lacking. This is particularly relevant as most pilots relate to residential (or private) charging rather than public charging [26,27]. Given that residential charging with one EV is more predicable than public charging (with several EVs with different charging characteristics on one charging station), applying smart charging on public charging infrastructure requires more research.…”
Section: Introductionmentioning
confidence: 99%
“…The shortest time required to charge the vehicle l Q u à l ð Þ The load transfer generated by the vehicle l K 1 The quadratic term coefficient of incentive-based demand response K 2…”
Section: Nomenclaturementioning
confidence: 99%
“…The uptake of electric vehicles (EVs) is rapidly growing around the world, 1 and the high penetration of EVs will potentially lead to high loads on current grids. Controlled charging of EVs will significantly affect the power grid load, 2,3 which can also provide an approach to deal with the high loads that the grid faces.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the optimal operation of the MG having ESSs have been investigated [6], [7], [16], [17], [8]- [15]. It has shown that BESS can effectively work as a solution for daily power intermittency and improve grid stability from many existing MGs test sites.…”
Section: Introductionmentioning
confidence: 99%